"A most excellent medicine": Malaria, Mithridate, and the death of Andrew Marvell. Issue 4 (4th July 2021) - Mottram, Stewart
ABSTRACT: The poet Andrew Marvell (1621–78) died suffering from vivax malaria, a common disease in the seventeenth century, endemic in estuary regions of eastern England. This article explores Marvell's death alongside the literature and history of malaria and malaria treatments in this period. Marvell was long assumed to have been poisoned by political enemies until the rediscovery in 1874 of Richard Morton's late seventeenth-century medical account, which blamed Marvell's death on medical incompetence, noting that the anti-malarial quinine would have saved him. The article uncovers important new findings in the Marvell archives, re-examining Morton's account in light of the manuscript, Hull History Centre, C DIAM/1 to argue that Marvell was in fact killed by the opiate, mithridate. The article offers new understanding of Marvell's death and of the popularity of opiates as malaria treatments in Marvell's day, of relevance to students of English literature, historical epidemiology, historical geography, and medical history.